1991
DOI: 10.1007/bf01055550
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of chlorothalonil to aquatic fauna and the impact of its operational use on a pond ecosystem

Abstract: Chlorothalonil is a fungicide whose heavy use in eastern Canada gives it the potential for significant aquatic contamination. Laboratory bioassays and field treatments of a pond system were undertaken to determine the toxic effects of chlorothalonil on aquatic fauna. The 96-h LC50 of technical chlorothalonil for rainbow trout (Oncorhynchus mykiss) was 76 micrograms/L and was not significantly different (p less than 0.05) from that of the formulated product (Bravo 500). The 96-h LC50 of Bravo 500 for blue musse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 17 publications
1
30
0
1
Order By: Relevance
“…It also depletes glutathione (GSH), a non-enzymatic reducing agent involved in cell detoxification (Tillman et al 1973). The effects of chlorothalonil on the survival of Daphnia magna (Ernst et al 1991;Fernández-Alba et al 2002) and the reproduction of the meiobenthic estuarine copepod Amphiascus tenuiremis (Bejarano et al 2005) are reported. Nitrofen, which is a diphenyl ether herbicide, interferes with thyroid hormone and/or retinoic acid signaling and induces organ damage (Manson 1986;Brandsma et al 1994;Mascrez et al 1998;Greer et al 2003) and it produces a spectrum of fetal abnormalities in rodents (Kling et al 2005).…”
Section: Abstract Behavioral Responses á Daphnia Magna á Toxic Characmentioning
confidence: 99%
“…It also depletes glutathione (GSH), a non-enzymatic reducing agent involved in cell detoxification (Tillman et al 1973). The effects of chlorothalonil on the survival of Daphnia magna (Ernst et al 1991;Fernández-Alba et al 2002) and the reproduction of the meiobenthic estuarine copepod Amphiascus tenuiremis (Bejarano et al 2005) are reported. Nitrofen, which is a diphenyl ether herbicide, interferes with thyroid hormone and/or retinoic acid signaling and induces organ damage (Manson 1986;Brandsma et al 1994;Mascrez et al 1998;Greer et al 2003) and it produces a spectrum of fetal abnormalities in rodents (Kling et al 2005).…”
Section: Abstract Behavioral Responses á Daphnia Magna á Toxic Characmentioning
confidence: 99%
“…Laboratory and field bioassays were conducted to determine the potential hazard chlorothalonil poses towards aquatic fauna. Rainbow trout (96-h LC 50 = 69 ug/L) was more sensitive than blue mussels (96-h LC 50 = 5.94 mg/L) and the water flea (48-h EC50= 97ug/L), when exposed under laboratory conditions (Ernst et al 1991). However, caged organisms, exposed under field conditions (aerially treated pond), were less sensitive, and exposed rainbow trout did not suffer any mortality.…”
Section: Aquatic Organismsmentioning
confidence: 89%
“…However, caged organisms, exposed under field conditions (aerially treated pond), were less sensitive, and exposed rainbow trout did not suffer any mortality. Ernst et al (1991) concluded that environmental factors such as, microbial degradation, dilution and adsorption to suspended matter reduced chlorothalonil's toxicity.…”
Section: Aquatic Organismsmentioning
confidence: 99%
“…Por muchos años el tributil-estaño (TBT) fue uno de los principios activos más usados en el mundo para la fabricación de pinturas anti-incrustantes (Ernst et al, 1991;Thomas, 2001;Thomas & Brooks, 2010) pero debido a su fuerte impacto en los ecosistemas acuáticos se ha regulado internacionalmente (EPC, 1998), dando paso a una nueva generación de alternativas, principalmente basadas en el óxido cuproso (Cu2O), pero que se acumula en sedimentos finos y anóxicos (Brooks & Mahnken, 2003), combinado con biocidas orgánicos (Burridge et al, 2010). Consecuentemente, altas concentraciones de estas sustancias han sido encontradas en estuarios y bajo balsas-jaulas de salmones y no existe suficiente información para evaluar el riesgo ambiental que puedan provocar.…”
Section: Introductionunclassified